Biomolecules from Orange and Grape Waste: Direct and Indirect Obtaining - Camargo, Dafne Angela [UNESP]; Pereira, Milene Stefani [UNESP]; Fleuri, Luciana Francisco [UNESP] (My University, 2022)
Orange and grape crops play a significant role in the Brazilian economy. Industrial processing generates large amounts of fruit wastes, which emerge as sources of enzymes and other bioactive compounds of interest in several studies due to their different biotechnological applications. The method adopted to obtain biomolecules plays an essential role in reducing costs with bioprocessing; thus, both isolated (direct use) and fermented (indirect use) waste types are seen as sustainable alternatives to chemical technologies. High commercial value enzymes such as phytases, lipases, and proteases are widely used in catalytic processes since they have versatile biochemical properties and broad applications. Their antioxidant, antiinflammatory, antimicrobial, antidiabetic, and cell modulation actions enhanced the biological potential of orange and grape waste. Therefore, this chapter emphasizes enzyme obtainment and the biomolecules mentioned above from orange and grape waste.
Keywords: Anti-inflammatory; Antidiabetic; Antimicrobial; Antioxidant; Cellular modulation activity; Citrus sinensis L. Osbeck; Lipases; Phytases; Proteases; V. labrusca; Vitis vinifera